Expectations for the Methodology and Translation of Animal Research: A Survey of the General Public, Medical Students and Animal Researchers in North America. Issue 4 (September 2016) - Joffe, Ari R.; Bara, Meredith; Anton, Natalie; Nobis, Nathan
To determine what are considered acceptable standards for animal research (AR) methodology and translation rate to humans, a validated survey was sent to: a) a sample of the general public, via Sampling Survey International (SSI; Canada), Amazon Mechanical Turk (AMT; USA), a Canadian city festival (CF) and a Canadian children's hospital (CH); b) a sample of medical students (two first-year classes); and c) a sample of scientists (corresponding authors and academic paediatricians). There were 1379 responses from the general public sample (SSI, n = 557; AMT, n = 590; CF, n = 195; CH, n = 102), 205/330 (62%) medical student responses, and 23/323 (7%, too few to report) scientist responses. Asked about methodological quality, most of the general public and medical student respondents expect that: AR is of high quality (e.g. anaesthesia and analgesia are monitored, even overnight, and 'humane' euthanasia, optimal statistical design, comprehensive literature review, randomisation and blinding, are performed), and costs and difficulty are not acceptable justifications for lower quality (e.g. costs of expert consultation, or more laboratory staff). Asked about their expectations of translation to humans (of toxicity, carcinogenicity, teratogenicity and treatment findings), most expect translation more than 60% of the time. If translation occurred less than 20% of the time, a minority disagreed that this would "significantly reduce your support for AR". Medical students were more supportive of AR, even if translation occurred less than 20% of the time. Expectations for AR are much higher than empirical data show to have been achieved.